2022
DOI: 10.1007/s00520-022-06931-9
|View full text |Cite
|
Sign up to set email alerts
|

Exercise in allogeneic bone marrow transplantation: a qualitative representation of the patient perspective

Abstract: Purpose Exercise is emerging as a vital aspect of care to alleviate the physical and psychosocial symptom burden associated with allogeneic bone marrow transplantation (BMT). Understanding the patient perspective regarding exercise is important to move towards implementation. This study aimed to characterise experiences and views regarding participation in an exercise program in adults receiving treatment for haematological disease with allogeneic BMT. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…In this sample, the most common reasons for not ordering rehabilitation therapies included lack of perceived need by the patient, lack of awareness of the clinical/rehabilitation team, and insurance coverage. Barriers for physical activity of cancer patients during hospital admission are complex and multifactorial 30-34. Influencing factors include patients’ perception that exercise/physical activity is not important and how the hospital environmental structure discourages physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sample, the most common reasons for not ordering rehabilitation therapies included lack of perceived need by the patient, lack of awareness of the clinical/rehabilitation team, and insurance coverage. Barriers for physical activity of cancer patients during hospital admission are complex and multifactorial 30-34. Influencing factors include patients’ perception that exercise/physical activity is not important and how the hospital environmental structure discourages physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, using the frequency, intensity, time, and type of specific resistance and aerobic exercises (FITT) framework could ensure that a specific exercise dosage is being delivered, optimizing the results of the exercise. 25 An exercise program should be tailored to specific symptoms and health needs of a population, 25,34 and the HSCT population has particular issues, such as decreased overall strength, gait, and balance impairments, reduced exercise capacity, sarcopenia, and malnutrition, among others. [1][2][3][4][5][6][7][8][9][10][11][12][13] Although there are no guidelines for the FITT components in the HSCT population, parameters from published randomized controlled trials involving the rehabilitation of hematological cancers could be adapted in HSCT patients.…”
Section: Exercise Therapy Characteristicsmentioning
confidence: 99%
“…Barriers to adherence to a group exercise intervention reported by participants included nausea, fatigue, weakness, severity of symptoms, emotional investment in others, and concern for infection risk. Facilitators included previous physical activity habits, accountability to staff and peers, explanation of the importance of exercise, access to exercise equipment and space, ability to follow progress, sense of community, and seeing peers do well (Abo et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Poor physical functioning and perceived loss of control are associated with worse psychosocial outcomes and quality of life in people undergoing stem cell transplantation [ 51 , 52 ]. Qualitative findings among people undergoing allogeneic transplantation highlight that exercise is perceived as positively influencing recovery from treatment and can provide a sense of control and structure during transplant [ 53 ]. Transplant recipients welcomed support from clinicians, resources to support exercise and measurement of physical outcomes and that these provided automatic incentives and motivation to exercise during transplant [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative findings among people undergoing allogeneic transplantation highlight that exercise is perceived as positively influencing recovery from treatment and can provide a sense of control and structure during transplant [ 53 ]. Transplant recipients welcomed support from clinicians, resources to support exercise and measurement of physical outcomes and that these provided automatic incentives and motivation to exercise during transplant [ 53 ]. Other qualitative literature specifically amongst myeloma ASCT recipients have also found that patients place importance on the role of exercise for enhancing recovery [ 11 , 12 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%